Prediction of response to anti-EGFR antibody-based therapies by multigene sequencing in colorectal cancer patients. Issue 1 (December 2015) - Lupini, Laura; Bassi, Cristian; Mlcochova, Jitka; Musa, Gentian; Russo, Marta; Vychytilova-Faltejskova, Petra; Svoboda, Marek; Sabbioni, Silvia; Nemecek, Radim; Slaby, Ondrej; Negrini, Massimo
Abstract Background The anti-epidermal growth factor receptor (EGFR) monoclonal antibodies (moAbs) cetuximab or panitumumab are administered to colorectal cancer (CRC) patients who harbor wild-typeRAS proto-oncogenes. However, a percentage of patients do not respond to this treatment. In addition to mutations in theRAS genes, mutations in other genes, such asBRAF, PI3KCA, orPTEN, could be involved in the resistance to anti-EGFR moAb therapy. Methods In order to develop a comprehensive approach for the detection of mutations and to eventually identify other genes responsible for resistance to anti-EGFR moAbs, we investigated a panel of 21 genes by parallel sequencing on the Ion Torrent Personal Genome Machine platform. We sequenced 65 CRCs that were treated with cetuximab or panitumumab. Among these, 37 samples were responsive and 28 were resistant. Results We confirmed that mutations in EGFR-pathway genes (KRAS, NRAS, BRAF, PI3KCA ) were relevant for conferring resistance to therapy and could predict response (p = 0.001). After exclusion ofKRAS, NRAS, BRAF and PI3KCA combined mutations could still significantly associate to resistant phenotype (p = 0.045, by Fisher exact test). In addition, mutations inFBXW7 andSMAD4 were prevalent in cases that were non-responsive to anti-EGFR moAb. After we combined the mutations of all genes (excludingKRAS ), the ability to predict response to therapy improved significantly (p = 0.002, by Fisher exact test). Conclusions The combination of mutations atKRAS and at the five gene panel demonstrates the usefulness and feasibility of multigene sequencing to assess response to anti-EGFR moAbs. The application of parallel sequencing technology in clinical practice, in addition to its innate ability to simultaneously examine the genetic status of several cancer genes, proved to be more accurate and sensitive than the presently in use traditional approaches.